Do Lateral Flows Matter for the Hyperresolution Land Surface Modeling?. Issue 22 (17th November 2017) - Ji, Peng; Yuan, Xing; Liang, Xin‐Zhong
Abstract: Hyperresolution land surface modeling provides an unprecedented opportunity to simulate locally relevant water and energy cycle, but lateral surface and/or subsurface flows that are essential at fine scale are often neglected by most one‐dimensional land surface models (LSMs). To analyze effects of lateral flows across scales, a Conjunctive Surface‐Subsurface Process model, which considers soil moisture‐surface flow interaction and quasi‐three‐dimensional subsurface flow, is implemented over a mountainous HyperHydro test bed in southwestern USA at different resolutions. Validation over more than 70 International Soil Moisture Network stations shows that there are significant improvements in soil moisture simulations from 30 km to 4 km as finer soil property and precipitation data are used, with correlation increased by 5%–16% and error decreased by 5%. Lateral surface flow has a significant influence on surface soil moisture and ground evaporation even at coarse resolution. Effect of lateral subsurface flow on soil moisture is nontrivial at 1 km or finer resolution especially over wet areas. At 100 m resolution, topography‐induced lateral subsurface flow causes drier peaks and wetter valleys, decreases latent heat by 8% at peaks, while increases it by 12% at valleys. Furthermore, influences of lateral subsurface flow on ground evaporation and vegetation transpiration are more significant during dry season due to a stronger coupling between soil moisture and evapotranspiration. Therefore, it is worthy to incorporate lateral flow processes in hyperresolution LSMs to better represent water and energy heterogeneity even with limited hyperresolution meteorological and surface data. Key Points: We analyze effects of lateral surface and subsurface flows on hyperresolution land surface modeling based on LSM simulations down to 100 m Lateral surface flow has significant influence on surface soil moisture and ground evaporation even at coarse resolution by reinfiltration Lateral subsurface flow becomes important for soil moisture and ET modeling at 1 km or higher resolution, especially during dry season